PENGARUH JUS MENTIMUN TERHADAP TEKANAN DARAH WANITA MENOPAUSE YANG HIPERTENSI DI DESA GAYAMAN KABUPATEN MOJOKERTO - Dhonna Anggreni (Jurnal Kesehatan dr. Soebandi, 2020)
Menopause is one of the most important periods of human life. Because in that period began to occur changes involving various systems and organs, the term cardiovascular system. Cucumber juice is one of the approved natural treatments that can reduce blood pressure in people with hypertension. This study tries to prove the effect of cucumber juice on blood pressure in hypertensive menopausal women. This research is an experimental study that provides cucumber juice which is drunk routinely for 1 week. Respondent's blood pressure was observed before and after being given help. Data collection techniques with purposive sampling were 20 respondents. The instrument used was the observation sheet and tensimeter.The results showed in the consultation group, most respondents answered moderate hypertension at the time of the initial examination. After giving cucumber juice for 1 week, obtained great results from respondents to reduce blood pressure to light with an average blood pressure to 151 mmHg. In the control group, most were still categorized as moderate hypertension with mean blood pressure of 169.6 mmHg. Mann Whitney test results about the difference between the control women and the experimental group after consuming cucumber juice for 1 week (Z count = -2.762 and p value = 0.005). Consumption of cucumber juice for 1 week regularly can reduce blood pressure in hypertensive menopausal women. Suggestion: hypertensive menopausal women need to routinely consume cucumber juice and carry out healthy living so that blood pressure becomes normal and controlled. Keywords: juice, cucumber, blood pressure, menopausal women.